Superior Vena Cava Syndrome and Multiple Venous Thrombosis in a Patient with B Cell Lymphoma - Mehmet Zahid Kocak; Gulali Aktas; Edip Erkus; Burcin Atak; Tuba Duman; Haluk Savli (Faculty of Medicine Universitas Padjadjaran, 2018)
Background: Superior vena cava syndrome (SVCS) develops due to external mechanical pressure of superior vena cava (SVC) by a mass lesion or by an enlarged lymph node, tumor invasion of the vessel wall, or venous thrombosis resulting in intraluminal obstruction. Approximately 3,9% of lymphomas are complicated with SVCS. This rate reaches to 7% in diffuse large B cell lymphoma. The objective of this article was to describe a case report of a young woman with a diffuse large B cell lymphoma, complicated with pericardial-pleural effusion and SVCS. Methods: A 25 year old woman referred to the Internal Medicine Clinic of Abant Izzet Baysal University Hospital with complaints of bloating in the neck and both arms. She had chest pain, dyspnea, cough, and epigastric discomfort for 10 days. A thoracic magnetic resonance imaging (MRI) test and pathological assessment were carried out.Results: A mediastinal mass 64x112x82 mm in size, displaced the heart and main mediastinal structures to posterior, was detected by thoracic magnetic resonance imaging (MRI) test. The result of the pathological assessment of the biopsy specimen revealed large B cell lymphoma, stained strongly and diffusely with CD20 and bcl-2. She was referred to the hematology unit and doing well after a chemotherapy.Conclusions: Diagnosis of SVCS requires high level of clinical suspicion, detailed and complete physical examination. Moreover, SVCS should be kept in mind in the differential diagnosis of patients presented with edema in the neck and upper extremities.